2021
DOI: 10.1002/jbm.a.37270
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture and preliminary evaluation of acellular tooth roots as allografts for alveolar ridge augmentation

Abstract: Alveolar ridge augmentation can be used to obtain appropriate alveolar ridge for dental implantation. A variety of bone graft materials including autogenous bone, allograft, xenograft, and alloplastic material are used in alveolar ridge augmentation. Autogenous tooth‐derived bone graft material has received much attention for the past few years, because the structure and physicochemical characteristics of tooth are similar to those of bones. Compared to autogenous tooth, allogenic tooth has the advantage of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Cytotoxicity analysis of ABGs through hemolysis and subcutaneous reactivity (such as arrhythmic lesions and edema) assays in inoculated rabbits revealed that ABGs show improved biocompatibility. Furthermore, micro-CT results revealed significant integration of tibia bone with ABGs during the 8-week treatment period, which was confirmed by H&E staining due to the absence of decalcified sections . However, presenting a commercial protocol in this field is difficult due to the potential effects of dental structure diversity (cementum, dentin, and enamel) and the variable thickness of its layers on acellularization approaches.…”
Section: Biomedical Applications Of Abgsmentioning
confidence: 85%
See 2 more Smart Citations
“…Cytotoxicity analysis of ABGs through hemolysis and subcutaneous reactivity (such as arrhythmic lesions and edema) assays in inoculated rabbits revealed that ABGs show improved biocompatibility. Furthermore, micro-CT results revealed significant integration of tibia bone with ABGs during the 8-week treatment period, which was confirmed by H&E staining due to the absence of decalcified sections . However, presenting a commercial protocol in this field is difficult due to the potential effects of dental structure diversity (cementum, dentin, and enamel) and the variable thickness of its layers on acellularization approaches.…”
Section: Biomedical Applications Of Abgsmentioning
confidence: 85%
“…10 As a result, the use of cell distribution techniques on the ABGs to stimulate the formation of small pieces of bone and uniform pores on the ABGs surface will be critical. Recently, to provide alveolar prominence for dental implants, Liu et al 66 planted the maxillary molar roots with the rabbit tibia after acellularizing them with SDS, Triton X-100, DNase, and RNase and sterilizing them with ethylene oxide. Cytotoxicity analysis of ABGs through hemolysis and subcutaneous reactivity (such as arrhythmic lesions and edema) assays in inoculated rabbits revealed that ABGs show improved biocompatibility.…”
Section: In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic bone graft materials, such as bioactive glass, have good biocompatibility and osteoconductivity, but are not osteoinductivity and slow absorption. Currently, the research on bone graft materials is in the ascendancy [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…First support for this approach came from preclinical studies [2][3][4] and case reports [4] followed by radiological analysis [5,6]. Preclinical research continues to better understand the process of graft consolidation [7,8] and acellular tooth root may even be used as allografts [9]. Clinical studies were performed supporting the use of autogenous tooth roots for augmentation of the alveolar bone [10] and before placing the implant [11].…”
Section: Introductionmentioning
confidence: 99%